Creating Social Connection Through Inferential Reproduction - Epley, Nicholas; Akalis, Scott; Waytz, Adam; Cacioppo, John T. (Psychological Science, 2008)
People are motivated to maintain social connection with others, and those who lack social connection with other humans may try to compensate by creating a sense of human connection with nonhuman agents. This may occur in at least two ways—by anthropomorphizing nonhuman agents such as nonhuman animals and gadgets to make them appear more humanlike and by increasing belief in commonly anthropomorphized religious agents (such as God). Three studies support these hypotheses both among individuals who are chronically lonely (Study 1) and among those who are induced to feel lonely (Studies 2 and 3). Additional findings suggest that such results are not simply produced by any negative affective state (Study 3). These results have important implications not only for understanding when people are likely to treat nonhuman agents as humanlike (anthropomorphism), but also for understanding when people treat human agents as non-human (dehumanization).